Kata practice and concepts according to highly experienced judo teachers and referees - Miranda, Mario Luiz; Julio, Ursula Ferreira; Calmet, Michel; Franchini, Emerson (Revista de Artes Marciales Asiáticas, 2012)
The objective of the present study was to characterize the kata practice among judo teachers, responsible by São Paulo State Federation’s kata competition and grade examinations. A closed questionnaire was applied to 20 teachers (male = 18; female = 2). The sample was 46 ± 10 years-old, with judo practice time of 34 ± 9 years, and graduation 5 ± 1 dan. Practice often varied from 2 (50%) to 4 (30%) sessions per month. Nage no kata was identified as the most performed (78%) and preferred (31%) kata, followed by katame no kata (25%), ju no kata (21%) and kime no kata (12%). Initiation of kata study usually started at the teacher’s dojo (79%) and through courses offered by state federation (21%). Practice is directed to techniques improvement (46%), complementation for judo training (29%), spiritualized/mental practice (14%) and for competition preparation (11%). The following attributes are the most important meanings given for kata: foundation (45%), essence (25%), origin (15%), form (10%) and principle (5%).